Tradisi Kenduri Perspektif Pendidikan Islam Multikultural - Lathifatul Izzah; Moh Ismail; Maskuri Bakri (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
This paper aims to interpret the kenduri tradition from the point of view of multicultural Islamic education. By focusing on three issues cover values, the internalization process, and the implications of internalizing the values of multicultural Islamic education. In this case the type of research used is qualitative with an ethnographic approach. The results show that the values ​​of multicultural Islamic education in kenduri can be classified into three groups, divine values, religious values, and social values. These values ​​can be internalized through awareness, knowledge transformation, skill development, habituation, inculcation of values, and finally habit or istiqoamah. This process is a stage of Islamic education that must be passed step by step to produce a complete person (kaffah). In the kenduri tradition, the internalization of the values ​​of multicultural Islamic education does not only involve the human element, but non-human elements are also needed, for example goals, methods, a comfortable environment, dialogue and cooperation with outsider. The process of internalizing the values ​​of multicultural Islamic education in the kenduri tradition that develops naturally has contributed to the development of cultural, socio-economic, and socio-religious arts to build and increase harmony and peace between citizens, and between citizens and the government.